The lncRNA CADM2-AS1 promotes gastric cancer metastasis by binding with miR-5047 and activating NOTCH4 translation - Zhang, Yu-Tong; Zhao, Li-Juan; Zhou, Teng; Zhao, Jin-Yuan; Geng, Yin-Ping; Zhang, Qiu-Rong; Sun, Pei-Chun; Chen, Wen-Chao (Frontiers in Pharmacology, 2024)
Abstract Background: Multi-organ metastasis has been the main cause of death in patients with Gastric cancer (GC). The prognosis for patients with metastasized GC is still very poor. Long noncoding RNAs (lncRNAs) always been reported to be closely related to cancer metastasis. Methods: In this paper, the aberrantly expressed lncRNA CADM2-AS1 was identified by lncRNA-sequencing in clinical lymph node metastatic GC tissues. Besides, the role of lncRNA CADM2-AS1 in cancer metastasis was detected by Transwell, Wound healing, Western Blot or other assays in vitro and in vivo. Further mechanism study was performed by RNA FISH, Dual-luciferase reporter assay and RT-qPCR. Finally, the relationship among lncRNA CADM2-AS1, miR-5047 and NOTCH4 in patient tissues was detected by RT-qPCR. Results: In this paper, the aberrantly expressed lncRNA CADM2-AS1 was identified by lncRNA-sequencing in clinical lymph node metastatic GC tissues. Besides, the role of lncRNA CADM2-AS1 in cancer metastasis was detected in vitro and in vivo. The results shown that overexpression of the lncRNA CADM2-AS1 promoted GC metastasis, while knockdown inhibited it. Further mechanism study proved that lncRNA CADM2-AS1 could sponge and silence miR-5047, which targeting mRNA was NOTCH4. Elevated expression of lncRNA CADM2-AS1 facilitate GC metastasis by up-regulating NOTCH4 mRNA level consequently. What's more, the relationship among lncRNA CADM2-AS1, miR-5047 and NOTCH4 was further detected and verified in metastatic GC patient tissues. Conclusions: LncRNA CADM2-AS1 promoted metastasis in GC by targeting the miR-5047/ NOTCH4 signaling axis, which may be a potential target for GC metastasis.